Does Inward Foreign Direct Investment Lead Export Performance in Pakistan? - Jawaid, Syed Tehseen; Raza, Syed Ali; Mustafa, Khalid; Abd Karim, Mohd Zaini (SAGE Publications, 2016)
This study is a pioneering attempt to investigate the impact of foreign direct investment (FDI) on export performance in Pakistan by using the long annual time series data from the period 1974–2012 and by using more rigorous econometric techniques. Autoregressive distributed lag-bound testing cointegration approach confirms the valid long-run relationship between considered variables. Results indicate the significant positive impact of FDI on real exports in long run as well as in short run. Results of Granger causality test, Toda and Yamamoto Modified Wald causality test and variance decomposition test confirm the bidirectional causal relationship between FDI and export performance in Pakistan. Results of rolling window analysis suggest that the coefficient of FDI in export model remains negative from 1983 to 1987, from 2001 to 2006 and in 2011. The coefficient of FDI in export model shows a positive coefficient in remaining years. It can be seen that FDI and real export are connected in complementary way in Pakistan. The policy makers should make policies that favour foreign investors so as to attract more FDI in Pakistan. It has been observed that a stable political and economic environment is desirable to attract more FDI in Pakistan.